CLINICAL STUDIES ON CEFETAMET PIVOXIL TO THE ODONTOGENIC INFECTIONS - MORISHIMA, TAKASHI; GOTO, JUN; YAMANE, NOBUO; MORIHANA, TAKEFUMI; SIGEHARA, SATOSHI; SASAKI, JIRO; UEMATSU, MASATAKA; SHIIKI, KAZUO; KANEKO, AKIHIRO; SAKAMOTO, HARUO; YAMAMOTO, TADASHI (CHEMOTHERAPY, 1990)
Cefetamet pivoxil (CEMT-PI) was administered at 250 mg b. i. d. or 500 mg b. i. d. to 97 patients with acute odontogenic infections and evaluated in 92 cases. The clinical efficacy rate, evaluated by the point method of the Japanese Society of Oral and Maxillofacial Surgeons, was 89.1%, and evaluated by the doctor in charge was 83.7%. Sixty-one strains were isolated from closed abscesses in 39 of 92 caces. Against 38 strains of aerobes and 23 strains of anaerobes, the antibacterial activity of cefetamet (CEMT) was compared with those of cefaclor (CCL), cefixime (CFIX), cefteram (CFTM) and ampicillin (ABPC). The MIC50 and MIC90 against oral streptococci were as follows, CEMT 0.39 μg/ml, 3.13μg/ml, CFIX 0.39μg/ml, 6.25μg/ml, CFTM 0.05μg/ml, 0.39μg/ml, CCL 0.78μg/ml, 1.56μg/ml, ABPC 0.025μg/ml, 0.05 μg/ml. No side effects were observed, but in the laboratory investigation, slightly elevated GPT was noted in one patient.